Epigenetic mechanisms of intrauterine fetal senescence: little-known effects of hyperhomocysteinemia during pregnancy - O. N. Bespalova; O. V. Pachuliia; A. P. Sazonova; Yu. P. Milyutina; E. A. Kornyushina; A. V. Korenevskiy (Акушерство, гинекология и репродукция)
Today, a whole body of evidence base has been formed showing the negative effect of hyperhomocysteinemia (HHC) during pregnancy on the intrauterine fetal development: risk factors associated with development of congenital neural tube defects, congenital heart defects and non-syndromic oral facial clefts. In addition, numerous studies have shown that HHC is a risk factor for serious pregnancy complications such as repeated pregnancy loss, preterm birth, preeclampsia, placental abruption, intrauterine growth restriction, gestational diabetes mellitus. At the same time, despite multiple clinical and experimental studies, the significance of HHC effects continues to support the interest to this issue. In recent years, new data were revealed about littleknown phenomena pregnancy-associated maternal HHC such as "epigenetic fetal aging" and "fetal atherogenesis". Epigenetic aging is an individual indicator of aging that captures interindividual differences at disease onset throughout life occurring during intrauterine development being reveaked as DNA hypomethylation. Moderate HHC during pregnancy causes fetal DNA hypomethylation, which, according to recent research, may represent the main mechanism underlying health in childhood and adulthood. "Fetal atherogenesis" is another understudied HHC effect emphasizing that the formation of atherosclerotic plaques begins not in adulthood, but in utero. A body of studies has shown that the formation of thickening and fatty streaks in vascular intima involved in the pathogenesis of atherosclerosis begins antenatally. The discovery of new aspects of negative intrauterine HHC impact on fetal development necessitates a detailed study of HHC causes as non-modifiable (genetic defects in enzyme systems), and more importantly, conditionally modifiable causes (lack of cofactors, excessive methionine consumption, medications) for their timely leveling. It is also important to study approaches to HHC correction at the preconception stage of a female reproductive function in order to correctly "program" fetus and newborn development.